Introduction to nuclear science - Bryan, Jeff C. (CRC Press, 2009)
Offers an introduction to nuclear chemistry and physics, spanning fundamental concepts, relevant mathematics, and applications in medicine, power generation, food safety, waste, and weapons. This book contains topics including energetics, radioactive decay, nuclear reactions, detection methods, health concerns, and safety measures.